Polyméry reagujúce na stimuly pre prípravu in situ gélov - Livovská, Simona; Gajdziok, Jan; Wolaschka, Tomáš; Vetchý, David (Chemické listy, 2021)
Recently, the stimuli-responsive polymers get increased scientific interest due to the ability to reversibly alter their physicochemical properties. They are often referred to as smart, environmental-sensitive or intelligent polymers. This review provides fundamental information on various types of smart polymers responsive to biological, physical and chemical stimuli with examples of their use in the preparation of smart hydrogels and in situ gels with controlled or targeted drug release.